MINAT DAN MOTIVASI MAHASISWA TERHADAP OLAHRAGA KARATE - Pratama, Rengga Siam; Simanjuntak, Victor Gaperius; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study is how much students interest and motivation for karate sports? The purpose of the study was to determine students' interests and motivations for karate sports. The research method is descriptive with a quantitative approach with the form of a survey. Data collection techniques use questionnaires or questionnaires. Data analysis used descriptive percentages. The population is a class of 2015-2016 as many as 177 people, while the sampling uses random or random, which is 25% of the 177 population of 45 people. The results showed that interest in karate sports was based on attitude indicators with an average of 3.54 (91.12%) good categories, ideals with an average of 2.52 (66.67%) enough categories, attention indicators with an average of 2.31 or (80%) enough categories. While the pleasure indicator with an average of 2.07 or (55%) the category is not good. Motivation towards karate sports based on parental indicators with an average of 3.24 (64.45%) in good categories, indicators of facilities and infrastructure with an average of 3.08 (53.33%) enough categories, friend indicators with an average 2.38 (93.33%) enough categories. While the environmental indicators with an average of 2.09 (66.67%) are not good categories.Keywords:. Interest, Motivation, Karate SportsÂ Â  Â